(untitled) (Journal of Engineering, 2015)
The concept of rehabilitation provided an essential richness in the conservation philosophy through sustaining buildings life and adapting them to the contemporary use through a vision which looks at the present and future . In Iraq , the existence of historical buildings and the traditional fabric in the cities required the urban development which enhanced the interests of planning and architectural fields especially the building rehabilitation which requires the architectural intervention , and all that led to elaborate the problem of research which is " The confusion in the concepts of monumental, historical and traditional buildings in Iraq, As well as The insufficient knowledge about rehabilitation and the acts related to it through the orientation of conservation in general, And the confusion between the levels of urban conservation and architectural conservation, and the challenges which accompany each of the urban rehabilitation and building rehabilitation in Iraqi reality in particular. And from this problem the research looks to Clarify the concepts of monumental, historical and traditional buildings and the nature of actions which are used to protect and sustain them, As well as Clarify the types of actions that are taken to protect those buildings through the orientations of rehabilitation and clarify the procedures, acts which are classified as policies, strategies and mechanisms. And Clarify the levels of rehabilitation on the urban level, and the architectural level (preserve and rehabilitate the single building) and their challenges in Iraq to find a formula that can solve the gap between the two levels.And to achieve these goals, the research put the theoretical framework and support it with the global experiences, which led to put a default perception represented by " It is possible to activate the rehabilitation of historical and traditional buildings in Iraq at medium scale between the major projects in urban renewal and the rehabilitation of individual building through a pilot projects to a group of buildings (traditional or historical have the connections on the urban level in the traditional fabric ". which provides a possible formula can be applied on the Iraqi reality. And get out the conclusions and recommendations from the research.